Phytic Acid Enhances Biocontrol Activity of Rhodotorula mucilaginosa against Penicillium expansum Contamination and Patulin Production in Apples - Yang, Qiya; Zhang, Hongyin; Zhang, Xiaoyun; Zheng, Xiangfeng; Qian, Jingya (Frontiers in Microbiology, 2015)
The effect of Rhodotorula mucilaginosa in combination with phytic acid (PA) on blue mold decay and patulin contamination of apples was investigated. Results from this study show that different concentrations of PA were effective in reducing the disease incidence of apples and that PA at concentration of 4 μmol/mL, decreased the incidence of blue mold decay in apples from 86.1% to 62.5%, and showed higher control efficacy compared to untreated, control fruit during storage at 20 °C. However, R. mucilaginosa combined with PA (4 μmol/mL) showed better control efficacy of blue mold decay than R. mucilaginosa used as single treatment, the disease incidence was reduced to 62.5% and lesion diameter on apples was reduced to 16.59cm. In in vitro experiments, the addition of PA enhanced the biocontrol effect of R. mucilaginosa against the growth of P. expansum and reduced patulin level when compared with either R. mucilaginosa or PA used separately. R. mucilaginosa together with PA, improved the inhibition of patulin production in wounded apples, decreasing the content of patulin by 89.6% compared to the control, under experimental conditions. Both R. mucilaginosa and R. mucilaginosa in combination with PA degraded patulin in vitro. In conclusion, the appropriate combination of R. mucilaginosa and PA may provide an effective biocontrol method for reducing postharvest decay of apples.